2010
DOI: 10.1098/rspb.2010.1772
|View full text |Cite
|
Sign up to set email alerts
|

Friction force reduction triggers feet grooming behaviour in beetles

Abstract: In insects, cleaning (grooming) of tarsal attachment devices is essential for maintaining their adhesive ability, necessary for walking on a complex terrain of plant surfaces. How insects obtain information on the degree of contamination of their feet has remained, until recently, unclear. We carried out friction force measurements on walking beetles Gastrophysa viridula (Coleoptera, Chrysomelidae) and counted grooming occurrence on stiff polymer substrata with different degrees of nanoroughness (root mean squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
6
22
0
Order By: Relevance
“…Similar effects have previously been demonstrated in other hairy attachment devices of flies (Peressadko and Gorb, 2004b), beetles (Peressadko and Gorb, 2004b;Voigt et al, 2008;Hosoda and Gorb, 2011;Bullock and Federle, 2011) and geckos (Huber et al, 2007). All these studies have revealed the presence of a so-called critical roughness, where contact forces were strongly reduced.…”
Section: Spatula Dimensions and Force Reductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Similar effects have previously been demonstrated in other hairy attachment devices of flies (Peressadko and Gorb, 2004b), beetles (Peressadko and Gorb, 2004b;Voigt et al, 2008;Hosoda and Gorb, 2011;Bullock and Federle, 2011) and geckos (Huber et al, 2007). All these studies have revealed the presence of a so-called critical roughness, where contact forces were strongly reduced.…”
Section: Spatula Dimensions and Force Reductionsupporting
confidence: 60%
“…However, the mechanism of adhesion reduction is not only based on the roughness itself but also may include some contamination effects Hosoda and Gorb, 2011) and adsorption of adhesive fluids Bauer and Federle, 2009;Gorb et al, 2010).…”
Section: Are Hairy Attachment Devices ʻOverbuiltʼ?mentioning
confidence: 99%
“…Under natural conditions, resilin is very likely always hydrated 28 . Beetles are known to produce tarsal liquids, which have been assumed to contribute to the adhesion capabilities by means of capillary processes 38,39 and cleaning effects 40,41 . Based on our assumption that the presence of high resilin concentrations in the setal tips increases the attachment ability of the adhesive pads, it becomes obvious that the hydration of resilin may be essential for keeping the attachment performance of the beetles on a high level.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and performance of tarsal attachment devices in both beetle species have previously been well studied (e.g. Peressadko and Gorb, 2004;Schuppert et al, 2005;Voigt et al, 2008;Voigt et al, 2010;Gorb and Gorb, 2009;Bullock and Federle, 2009;Bullock and Federle, 2011;Clemente et al, 2010;Hosoda and Gorb, 2011;Prüm et al, 2012). Both species bear spatula-shaped lanceolate and filament-shaped tarsal adhesive setae in males and females, and additionally setae with discoid terminal tips only in males (Stork, 1980a;Pelletier and Smilowitz, 1987).…”
Section: Materials and Methods Insectsmentioning
confidence: 99%